2018
DOI: 10.1210/jc.2017-01695
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hypoglycemia After Gastric Bypass vs Sleeve Gastrectomy: A Randomized Trial

Abstract: We show that reactive hypoglycemia is no less common after SG and is not a safer option than RYGB, but RYGB is associated with more severe hypoglycemic episodes. This is likely due to the lack of improvement of β-cell sensitivity to changes in circulating glucose after RYGB, which determines an inappropriately high insulin secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 37 publications
4
59
1
2
Order By: Relevance
“…These findings are in accordance with two previous studies using questionnaires (13,28). In contrast, MMTT was found in our study to be much more in the RYGB procedure group compared with the SG group and demonstrated that the first group exhibited a more prolonged high insulin secretion even when glucose concentrations were falling (15). Other mechanisms that can contribute to the higher rate of severe PBH after bypass interventions include: accelerated nutrient emptying from the stomach pouch into the intestine (roux limb), leading to increased postprandial hyperglycemic peak and subsequently enhanced enteroinsulin axis activity, mediated by massive GLP-1 secretion; altered bile acid metabolism, and diminished insulin clearance (9).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…These findings are in accordance with two previous studies using questionnaires (13,28). In contrast, MMTT was found in our study to be much more in the RYGB procedure group compared with the SG group and demonstrated that the first group exhibited a more prolonged high insulin secretion even when glucose concentrations were falling (15). Other mechanisms that can contribute to the higher rate of severe PBH after bypass interventions include: accelerated nutrient emptying from the stomach pouch into the intestine (roux limb), leading to increased postprandial hyperglycemic peak and subsequently enhanced enteroinsulin axis activity, mediated by massive GLP-1 secretion; altered bile acid metabolism, and diminished insulin clearance (9).…”
Section: Discussionsupporting
confidence: 94%
“…Only a minority of individuals in our study reported symptoms suggestive of hypoglycemia based on questionnaires. Furthermore, during MMTT-DOI:10.4158/EP-2019-0185 © 2019 AACE.induced hypoglycemia, only a quarter complained of symptoms even when experiencing severe hypoglycemia.Our findings are in accordance with previous studies(15,17) and are supported by the intriguing findings of Abramsson et al that examined twelve non-diabetic obese patients with hyperinsulinemic-hypoglycemic clamp before and 6 months post gastric-bypass procedure. The study demonstrated significant attenuation of postsurgery hypoglycemic symptoms and marked reduction in glucagon, cortisol, catecholamines levels and in the sympathetic response to hypoglycemia(27).Hypoglycemia unawareness may also provide a plausible mechanism contributing to the unexplained previous reports of a higher rate of car accidents, suicide attempts and even mortality in individuals who underwent BS(2)(3)(4)(6)(7)(8).…”
supporting
confidence: 94%
See 2 more Smart Citations
“…Postbariatric hypoglycaemia (PBH), formerly also described as late dumping, is a significant but under-recognized medical complication after bariatric surgery [1,2]. Depending on the diagnostic test, recent data suggest higher incidence rates than previously thought, occurring in up to 48% of patients after Roux-Y gastric bypass and up to 25% of patients after sleeve gastrectomy [3][4][5].…”
Section: Introductionmentioning
confidence: 99%